Syzygium campanulatum korth methanolic extract inhibits angiogenesis and tumor growth in nude mice - Abdalrahim , FA Aisha; Zhari I, Ismail; Khalid , M Abu-Saleh; Siddiqui, Mohammad Jamshed Ahmad; Ghafar, Gheniya; Shah, Amin Malik (BioMed Central, 2013)
Betulinic acid was isolated from methanolic extract by crystallization and chromatography techniques. S.C. methanolic extract was analyzed by UV-Vis spectrophotometry, FTIR, LCMS, and HPLC. Antiangiogenic effect was studied on rat aortic rings, matrigel tube formation, cell proliferation and migration, and expression of vascular endothelial growth factor (VEGF). Antitumor effect was studied using a subcutaneous tumor model of HCT 116 colorectal carcinoma cells established in nude mice. Results Analysis by HPLC, LC-MS and FTIR confirm presence of betulinic acid in S.C. methanolic extract. Quantitative analysis by HPLC indicates presence of betulinic acid in S.C. extract at 5.42 ± 0.09% (w/w). Antiangiogenesis study showed potent inhibition of microvessels outgrowth in rat aortic rings, and studies on normal and cancer cells did not show any significant cytotoxic effect. Antiangiogenic effect was further confirmed by inhibition of tube formation on matrigel matrix that involves human endothelial cells (IC50 = 17.6 ± 2.9 μg/ml). S.C. extract also inhibited migration of endothelial cells and suppressed expression of VEGF. In vivo antiangiogenic study showed inhibition of new blood vessels in chicken embryo chorioallantoic membrane (CAM), and in vivo antitumor study showed significant inhibition of tumor growth due to reduction of intratumor blood vessels and induction of cell death. Conclusion Collectively, our results indicate S. campanulatum as antiangiogenic and antitumor candidate, and a new source of betulinic acid.